Sistem Pendukung Keputusan Peserta Lomba Desain Logo Menggunakan Metode Simple Additive Weighting (SAW) Berbasis Website - Habibur Rahman Arjuni; Arif Senja Fitrani (Explorer, 2022)
The Faculty of Business, Law and Social Sciences (FBHIS) Universitas Muhammadiyah Sidoarjo (Umsida) held an FBHIS Logo Design Competition for the FBHIS creative community. The provisions of the competition are to represent all study programs (Prodi) in FBHIS, namely Management Study Program, Master of Management, Law, Communication Studies, Public Administration, Accounting, and Digital Business. To help determine the winner of the best contestants, a decision support system (SPK) is needed that is able to provide alternative solutions to the parties concerned. The method used in the decision support system for selecting participants in the logo design competition uses the Simple Additive Weighting (SAW) method for the weighting of the criteria. The software used in making DSS is MySQL and PHP. The assessment criteria are taken from the Originality selection test scores, Design Idea Concepts, Aesthetic Values, Conformity of Themes and Messages Delivered. Alternative samples were taken as many as 20 participants with the top rank. The results of the SAW calculation give the order of the participants' scores from the highest to the lowest. The result of the SPK is not a final decision, because it goes back to the one who made the decision